RADEC: INDONESIAN-BASED LEARNING MODEL IN IMPROVING STUDENTS' UNDERSTANDING OF NARRATIVE MATERIALS AT MAN 5 JOMBANG (BEST PRACTICE) - Kiswati; Vicky Galih Dewangga; Moh. Rodli; Hari Prastyo (JEELL (Journal of English Education, Linguistics and Literature), 2025)
Grammar is one of the important components of English but many students find it difficult to understand it, including students of MAN 5 Jombang. The researcher conducted a study by implementing the RADEC learning model (Read, Answer, Discuss, Evaluate, Create) which aims to improve the understanding of "grammar" in the material of interactional transactional text. RADEC is a new learning model created by lecturers at UPI Bandung which is adjusted to the current era of education in Indonesia. This article is a best practice that proves that the RADEC learning model has succeeded in improving students' understanding of "grammar" with evidence that all student scores have increased.